Soul work and giving back. Ethnic Support Groups and the Hidden Costs of Social Mobility: Lessons from Hungarian Roma Graduates - Durst, Judit; Nyírő, Zsanna (Intersections. East European Journal of Society and Politics, 2018)
For a long time, social and public policies have presented upward social mobility as an unambiguously progressive process. However, there is a relatively new line of academic research that concerns the dilemmas, or ‘hidden costs’, of upward mobility. Still, apart from a few inspiring exceptions, there is a lack of empirical studies, especially in Hungary, that explore the personal experiences of the impact of moving class through educational mobility. Academic literature about stigmatised, disadvantaged minorities such as Afro-Americans and Mexicans in the U.S or the Roma in Europe suggests that the professional middle class of these groups – those who have demonstrated an exceptional range of intergenerational mobility – have adopted a distinctive upward mobility strategy to overcome the challenges that are unique to them. These challenges emerge from the difficulties of maintaining intra-class relations with poorer ‘co-ethnics’ (people from the communities they were brought up in), but also managing interethnic relations with the ‘white’ (non-Black in the U.S, non-Roma in East-Central Europe) majority. As part of this minority culture of mobility, the Roma, as with other stigmatised minority groups, create and join ethnic professional organisations to enable them to culturally navigate both worlds. Throughout this paper, we focus our attention on influential ethnic support groups or organisations and address the question what effect they have on the costs of upward mobility in the case of our Roma professional middle-class sample.